IMPLEMENTATION OF THE POLICY ON RETRIBUTION FOR PARKING SERVICES ON PUBLIC ROADS IN THE BANGKO DISTRICT OF THE ROKAN HILIR REGENCY - Widyasti, Hasi Wahyu; Habibie, Dedi Kusuma (TOPLAMA, 2025)
The Department of Transportation of Rokan Hilir Regency implements a parking service retribution policy for on-street parking as one of the sources of Local Own-Source Revenue (PAD) and a form of public service to the community. However, the implementation of this policy has not been optimal, as indicated by the low use of parking tickets, inconsistent retribution rates in the field, and weak supervision and coordination among the implementing parties. This study aims to describe the implementation of the parking retribution policy in Bangko Sub-district and to identify the obstacles encountered in its execution. This research employs a descriptive qualitative method and applies George C. Edward III's implementation theory, which includes aspects of communication, resources, disposition, and bureaucratic structure. The results show that communication is the most dominant obstacle, followed by limited resources and the suboptimal role of bureaucracy in supervision. Therefore, improvements are needed through enhanced public outreach, staff training, provision of supporting facilities, and strengthened coordination to ensure effective policy implementation and a tangible impact on public service and local revenue.